How Does Global Economic Policy Uncertainty And Macroeconomics Interact With Sovereign Retail Sukuk Yield? Evidence From Indonesia - Idham Chalid, Fitria; Zubaidah, Siti; Zahara, Jihan Nabila (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
This study aims to analyze empirically the effect of macroeconomics variable, and uncertainty of global economic policies on the yield of sovereign retail sukuk in the short term. Sampling of Retail Sukuk Series 010 (SR010) uses purposive sampling method by considering that SR010 is the sukuk with the lowest yield and volume of issuance during the previous three years and the previous two years. Data analysis used in this study using ARDL-ECM after going through the stationarity test and cointegration test. The results show that in the long term inflation and exchange rate variables have a significant influence on the yield of retail sukuk SR010, while the variables for profit sharing on mudharabah deposits and global policy uncertainty have no significant effect on the yield of retail sukuk SR010. On the other hand, in the short term, the variable for profit sharing on mudharabah deposits in the previous period and significant uncertainty over the policies of the previous period, which affected the yield of retail sukuk SR010, had no effect on inflation and exchange rates. These empirical findings are expected to be a reference for investors to make decisions in choosing SUKRI as their investment portfolio, as well as a consideration for the government in macro policies in Indonesia